2008
DOI: 10.1111/j.1365-2656.2008.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in population growth rate and community structure affects local and regional dynamics

Abstract: Summary 1.Theory predicting that populations with high maximum rates of increase ( r max ) will be less stable, and that metapopulations with high average r max will be less synchronous, was tested using a small protist, Bodo , that inhabits pitcher plant leaves ( Sarracenia purpurea L.). The effects of predators and resources on these relationships were also determined. 2. Abundance data collected for a total of 60 populations of Bodo , over a period of 3 months, at six sites in three bogs in eastern Canada, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…This might be explained by the high sensitivity (or lower resistance) to environmental variations of “fast” species compared with “slow” ones (Li et al, 2021). In a spatially correlated environment, local populations of “fast” species track environmental fluctuations more closely and thereby exhibit higher spatial synchrony (Trzcinski et al, 2008). Alternatively, the trend in neighborhood synchrony along the fast–slow spectrum may be complicated by time series length in empirical data.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the high sensitivity (or lower resistance) to environmental variations of “fast” species compared with “slow” ones (Li et al, 2021). In a spatially correlated environment, local populations of “fast” species track environmental fluctuations more closely and thereby exhibit higher spatial synchrony (Trzcinski et al, 2008). Alternatively, the trend in neighborhood synchrony along the fast–slow spectrum may be complicated by time series length in empirical data.…”
Section: Discussionmentioning
confidence: 99%
“…; Hammill et al . ) and other phytotelmata (Kneitel & Miller ; Trzcinski, Walde & Taylor , ). In our study, we found that filter feeder survival (and abundance) decreased virus counts ( r = −0·34, P = 0·002), bacterial densities ( r = −0·40, P = 0·002), algal densities ( r = −0·25, P = 0·02), log ciliate densities ( r = −0·60, P < 0·001) and water turbidity ( r = −0·24, P = 0·03).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is only in the multiyear analysis that differences between forests and forest openings become evident. Environmental conditions fluctuate between these two habitat types but in our study were so similar that these differences cannot be detected by one year of data collection (Schooley, 1994; Adler and Drake, 2008; Trzcinski et al, 2008).…”
Section: Discussionmentioning
confidence: 47%